2011
DOI: 10.1074/jbc.m110.216655
|View full text |Cite
|
Sign up to set email alerts
|

High Mannose-binding Lectin with Preference for the Cluster of α1–2-Mannose from the Green Alga Boodlea coacta Is a Potent Entry Inhibitor of HIV-1 and Influenza Viruses

Abstract: The complete amino acid sequence of a lectin from the green alga Boodlea coacta (BCA), which was determined by a combination of Edman degradation of its peptide fragments and cDNA cloning, revealed the following: 1) B. coacta used a noncanonical genetic code (where TAA and TAG codons encode glutamine rather than a translation termination), and 2) BCA consisted of three internal tandem-repeated domains, each of which contains the sequence motif similar to the carbohydratebinding site of Galanthus nivalis agglut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 62 publications
1
67
0
Order By: Relevance
“…This lectin family includes: OAA from Oscillatoria agardhii NIES-240 Sato and Hori, 2009;Koharudin et al, 2011), PFL from Pseudomonas fluorescens Pf0-1 (Sato et al, 2012), MBHA from Myxococcus xanthus (Koharudin et al, 2012), BOA from Burkholderia oklahomensis (Whitley et al, 2013), KAA-2 from Kappaphycus alvarezii (Sato et al, 2011a), BCA from Boodlea coacta (Sato et al, 2011b) and ESA-2 from Eucheuma serra (Sato et al, 2015). All of them share binding specificity for high-mannose N-glycans and have commonly two or four tandem repeats consisting of highly conserved sequences, which may lead to subtle difference in the degree of inhibiting activities.…”
Section: Introductionmentioning
confidence: 99%
“…This lectin family includes: OAA from Oscillatoria agardhii NIES-240 Sato and Hori, 2009;Koharudin et al, 2011), PFL from Pseudomonas fluorescens Pf0-1 (Sato et al, 2012), MBHA from Myxococcus xanthus (Koharudin et al, 2012), BOA from Burkholderia oklahomensis (Whitley et al, 2013), KAA-2 from Kappaphycus alvarezii (Sato et al, 2011a), BCA from Boodlea coacta (Sato et al, 2011b) and ESA-2 from Eucheuma serra (Sato et al, 2015). All of them share binding specificity for high-mannose N-glycans and have commonly two or four tandem repeats consisting of highly conserved sequences, which may lead to subtle difference in the degree of inhibiting activities.…”
Section: Introductionmentioning
confidence: 99%
“…The homology sequence analysis of BPL-3 showed that it might belong to H lectin group from Roman snails (Helix pomatia). The latest primary structure published was of lectin from Boodlea coacta (BCA) [105]. BCA consisted of 3 internal tandem-repeated domains, each one containing the sequence motif similar to the carbohydrate-binding site of land plant lectin from Galanthus nivalis.…”
Section: Marine Algae Lectinsmentioning
confidence: 99%
“…They are classified into many groups based on amino acid sequences. For example, galectin, and C-type lectin are popular lectins (Kasai & Hirabayashi, 1996;Drickamer, 1999), and even today, various lectins with new structures are still being found in many animals, bacteria, and fungi ( Jimbo et al, 2005;Tateno et al, 1998;Jimbo et al, 2000;Sato et al, 2011).…”
Section: Introductionmentioning
confidence: 99%